A NUMERICAL-EXPERIMENTAL STUDY OF THE AIR ENTRAINMENT FOR SELF ASPIRING BURNERS - Baldani, L. S.; Zdanski, P. S. B. (Revista de Engenharia Térmica, 2016)
This work presents an experimental and numerical study addressing the effects of air entrainment for self aspiring burners. Within this framework, the work focus on the analysis of four different burners tested with four different nozzles, resulting in a total of sixteen different configurations. The gas used for the tests was methane. Each nozzle diameter provided a different flow rate, which also resulted in a different entrainment, therefore a different oxygen concentration on the ports area, which was measured using an oxygen sensor. The level of oxygen decreased with the increase of the flow rate of the gas, and had a linear behavior with the nozzle diameter. The finite volume method with the realizable k-ε model was then applied to numerically investigate this phenomenon using the commercial software STARCCM+. The results shows that for the sixteen points tested the worst correlation had a relative error of 2.95%, while for the best one was of 0.04%.